Effects of curing pressure on mode II fracture toughness of uni-directional GFRP laminates. (December 2015) - Sajith, S.; Arumugam, V.; Dhakal, H.N.
Abstract: The purpose of this work is to investigate the effect of curing pressure on the Mode II interlaminar fracture toughness behaviour of uni-directional glass fibre reinforced plastics (GFRP). Investigation was carried out experimentally on uni-directional GFRP specimens using end notched flexure (ENF) tests to find out the changes in the material and geometric properties due to the application of pressure. Stiffness of the different laminates cured under different pressure was studied and it was shown that both material and geometric stiffness accounts for the total stiffness of the laminate, but their contribution to total stiffness varies. It is shown that fracture toughness values, G IIC, remain unaffected by stiffness since it is only related to the new surfaces created due to crack initiation and propagation. It is shown that the thickness of the matrix layer influences all the properties, including the fracture toughness. The laminates cured at 5 Psi, 400 Psi and 800 Psi exhibit different fracture toughness. Optimum thickness of matrix layer offers both adhesive and cohesive resistance to the crack propagation and thus offers high fracture resistance.